2006
DOI: 10.1536/ihj.47.409
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Markers of Inflammation and Brachial-Ankle Pulse Wave Velocity in Japanese Men

Abstract: SUMMARYThe objective of the present study was to examine the relationship between markers of inflammation, such as high-sensitivity C-reactive protein (hsCRP) and erythrocyte sedimentation rate (ESR), and brachial-ankle pulse wave velocity (baPWV), an indicator of arterial stiffness, in Japanese men.We studied 269 male subjects (mean age, 53 years) who entered our health check-up program. Subjects who were receiving any medication were excluded from the study. baPWV was measured using a volume-plethysmographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Recently, numerous studies have indicated that inflammation increases arterial stiffness (32)(33)(34)(35)(36). However, in the current study the SDPTG indices were not independently associated with the blood leukocyte count or serum CRP levels.…”
Section: Discussioncontrasting
confidence: 86%
“…Recently, numerous studies have indicated that inflammation increases arterial stiffness (32)(33)(34)(35)(36). However, in the current study the SDPTG indices were not independently associated with the blood leukocyte count or serum CRP levels.…”
Section: Discussioncontrasting
confidence: 86%
“…Notwithstanding this controversy, CRP remains an important marker to include when investigating CVD development. Various studies report an association between CRP and PWV [10,[36][37][38] but in some, these associations disappear after adjustment for conventional risk factors for CVD [37,39,40]. There are also studies that have reported no association between CRP and PWV [41,42], and it is possible that CRP does not have a causal role in the development of arterial stiffness but may only act as a marker of vascular damage [43].…”
Section: Discussionmentioning
confidence: 99%
“…The distance (L) between the heart and sampling points was calculated automatically according to the subject's height. baPWV was calculated according to the following formula: baPWV = L/T(L = La-Lb, where La is the path length from the heart to ankle, and Lb is the path length from the heart to brachium) [26]. In the present study, the measurement of baPWV was performed on a different occasion from the blood collection so that the participant would be mentally relaxed.…”
Section: Arterial Stiffness Measurementmentioning
confidence: 99%